Function of Aizuchi in The Podcast as One of Digital Communication Media - Salsabila Putri Perdana; Hety Nurohmah (IZUMI, 2022)
unintentionally. Because communication is essential, the use of language becomes the main thing for social life. In line with this, the use of language in each nation also has its characteristics. One is in Japan, which has a unique way of communicating, Aizuchi. Aizuchi is a form of response so that the speaker feels heard and understood by the listener. In this era of globalization, when technology is increasingly sophisticated, it is also easier for humans to communicate through podcast media as one of the audiovisual media that can be listened to anywhere and anytime because the platform for listening or watching it is straightforward to access. This study's data source was taken from the Yuyu no Sekai Podcast in the episode "[Gesuto: Chō-san] Vol. 01 - Myanmā tte don'na kuni?". This study aims to find out the differences in the use of aizuchi in Japanese and Myanmar people fluent in Japanese in the episode "[Gesuto: Chō-san] Vol. 01 - Myanmā tte don'na kuni?". The theory used in this researchis the theory of Mayumi Kutoba. This research method uses a descriptive qualitative type, with the collection method being the listening and Simak Bebas Libat Cakap listening techniques. The data contained in this study amounted to 51 data divided into 10 Kiiteiru to iu shingou functions, 14 Rikaishiteiru to iu shingou functions, 10 Doui no shingou functions, 9 Kanjyou noshingou functions, 6 Ma wo motaseru shingou functions, 1 Hitei no shingou function and 1 Jyouhou wo tsuika, teisei, youkyuu no shingou function. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor